Hydroxyapatite and Biopolymer Composites with Promising Biomedical Applications - Flores Valdez, Juanita Daria; Sáenz Galindo, Aidé; López Badillo, Claudia Magdalena; Castañeda Facio, Adali Oliva; Acuña Vazquez, Pablo (Revista Mexicana de Ingenieria Biomedica, 2022)
The purpose of tissue engineering (regenerative medicine) is to develop materials that replace human tissue, having as main characteristics’ biodegradability, biocompatibility, no toxicity, osteoconductivity, which lead to cell maturation and proliferation. Due to the importance of the development of this type of materials, several researchers have used biopolymers and calcium phosphate salts (hydroxyapatite) as composites to be used in this area as drug releases, scaffolds, implants, among others. Different biopolymers can be suitable for this type of application, in this work we have described the most widely used biopolymers for biomedical purposes, such as alginate, collagen, gellan gum, chitosan, and polylactic acid, in addition to a detailed description of hydroxyapatite, biopolymers, as well as biopolymer/hydroxyapatite composites, to highlight their potential and the most relevant characteristics of these materials.